Cost of energy infrastructure in Europe and Austria: electricity, gas, oil, and heat. (17th February 2022) - Ahamer, Gilbert
The present research analysis of over 250 pieces of literature identifies the cost of energy networks. a) The basic question is: what does the energy infrastructure cost now?; b) The further perspective is: how much will energy networks cost in the future when achieving the climate protection goals by an energy transition? For the target of cost finding estimates, the current Austrian projects to construct new energy lines are used because cost data can be retrieved for them. Network costs are (as a mean with a wide spread within the energy sources): electricity: 1.5 M/km to 3 M/km, with an average of 2.3 M/km; gas: 0.5 M/km to 2.5 M/km (mainly depending on the pipe diameter), oil: 1.6 M/km; and heat: 0.2 to 1.8 M/km. Overall, a very rough estimate for all four energy carriers is: around 2 M/km (i.e., ~1+1 M/km each for line-oriented + point-oriented costs, such as transformer stations).